Mobile Technology Use and Desired Technology-Based Intervention Characteristics among HIV+ Black Men Who Have Sex with Men - Senn, Theresa E. (AIDS Care, 2016)
HIV positive Black men who have sex with men (MSM) are retained in HIV medical care at suboptimal rates. Interventions targeted to Black MSM are needed to help to improve their retention in care. The purposes of this study were to investigate the use of mobile technology among HIV+ Black MSM and to explore participants' thoughts about the use of mobile technology for HIV retention in care interventions. Twenty-two HIV+ Black MSM completed a technology use survey and participated in a qualitative interview regarding technology-based interventions. The majority of participants (95%) had access to a cellphone, and used their phones frequently (median 3 hours/day). Men preferred interventions that would allow for anonymous participation and that would provide individually-tailored support. Mobile technology is a promising approach to intervention delivery for both younger and older HIV+ Black MSM. These interventions should incorporate features that are desirable to men (i.e., anonymous participation and individual tailoring).